2008
DOI: 10.1021/jp077604a
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study of Polarization Effects on AgI

Abstract: Three different models of AgI are studied by molecular dynamics simulations. The first one is the rigid ion model (RIM) with the effective pair potential of the Vashishta and Rahman form and the parametrization proposed by Shimojo and Kobayashi. The other two are polarizable ion models in which the induced polarization effects have been added to the RIM effective pair potential. In one of them (PIM1), only the anions are assumed to be polarizable by the local electric field. In the other one (PIM2s), the silve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 56 publications
4
29
0
Order By: Relevance
“…It is difficult to explain why the E a for molten CuI is larger than that for AgI by considering the difference in the ionic size and mass between Ag and Cu, because an Ag ion is larger and heavier than a Cu ion, which seems to be a disadvantage for the ionic diffusion. Furthermore, the valence charges of Ag and Cu ions are almost the same [12,13]. However, the concentration dependence of E a for (AgI) 1-x (CuI) x mixtures observed in this study would not be the error, because the similar behavior has also been reported for the solid solution of AgI-CuI system [5].…”
supporting
confidence: 74%
See 1 more Smart Citation
“…It is difficult to explain why the E a for molten CuI is larger than that for AgI by considering the difference in the ionic size and mass between Ag and Cu, because an Ag ion is larger and heavier than a Cu ion, which seems to be a disadvantage for the ionic diffusion. Furthermore, the valence charges of Ag and Cu ions are almost the same [12,13]. However, the concentration dependence of E a for (AgI) 1-x (CuI) x mixtures observed in this study would not be the error, because the similar behavior has also been reported for the solid solution of AgI-CuI system [5].…”
supporting
confidence: 74%
“…Furthermore, weak covalencies of cation-cation pairs have also been reported [14,15], and finally the resulting first correlation lengths of cationcation and cation-I correlations are different for molten AgI and CuI [16]. Moreover, it has been reported that the electric field generated from the dipole-moment of anions affects the liquid structure and cationic diffusion in molten Ag and Cu halides [12,13,[17][18][19]. These complex properties of Ag and Cu halides compared to typical molten salts might be associated with the activation energy in AgI-CuI system.…”
mentioning
confidence: 96%
“…36-38 They were also used by Trullas and co-worker to study a series of silver and copper halides, [39][40][41][42][43] and the PIM model now is implemented in the CP2K code. 44 Going back to the case of oxides, when attention is restricted to a single phase or where similar materials are being compared it is often sufficient to neglect the full complexity of the AIM model, and we have also successfully used some PIM-type potentials in the case of amorphous GeO 2 45,46 and of doped zirconia crystals.…”
Section: Interaction Potentialsmentioning
confidence: 99%
“…Although we used the rigid ion model in this study, if we consider a polarizable ion model, the cation diffusion would become large. However, polarization effects on NaI, RbI, and their mixture would be weak compared to silver (or cupper) halides [13][14][15][16][17][18][19][20] and zinc halides [21,22]. Ciccotti et al have reported that D Na and D I for pure NaI at 1081K are 9.4 × 10 -5 and 6.8 × 10 -5 cm 2 /s, respectively [3].…”
Section: " ! "mentioning
confidence: 99%